Marketing plan of a christian-themed cafe. - Lim, Cindy Sin Yee. (2008)
This is an entrepreneurial exploratory project to devise a marketing plan for a Christian-themed caf?. It is a multi-disciplinary project, covering the fields of marketing, finance, theology and psychology. The project contributes in bridging the information gap between the fields of retailing and religion/ spirituality.